Internet use and teacher planning: potential problems and advantages - Mutlow, Hannah (2014)
The purpose of this study was to establish some of the ways in which teachers use the internet as a lesson planning tool and also to analyse what effects this use might have on their planning. The literature review highlighted the severe lack of academic writing in this specific area. This mixed methods study involved the use of a questionnaire survey and diary keeping by a number of participants, as well as semi-structured interviews. The findings suggest that the potential problems and advantages of teacher use of the internet are very closely related to each other. Indeed, they are so intertwined as to be almost inextricable